2019
DOI: 10.3389/fmicb.2019.01243
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Enhanced Oil Recovery by Alkylbenzene-Oxidizing Nitrate-Reducing Bacteria

Abstract: Microbially enhanced oil recovery (MEOR) of heavy oil and bitumen is challenging because light hydrocarbons, which can feed resident microbial communities are present in low concentrations, if at all. We have recently shown that increasing the toluene concentration of heavy oil by aqueous injection followed by injection of nitrate boosts the activity of toluene-oxidizing nitrate-reducing bacteria in heavy oil-containing sand pack columns, giving production of residual oil in place (ROIP). In the current work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In contrast, strain NS1 exhibited similarities to a PO type of DRP and transient accumulation of NO 2 − resulting from reduction of NO 3 − (Figure 1B). This strain is phylogenetically more related to strains K172 and S100 ( > 90% 16S rRNA gene similarity; Suri et al, 2019) but unexpectedly showed lower denitrification rates as compared to the type strain K172 under identical denitrifying culture conditions. At higher NO 3 − concentrations ( > 2 mmol L −1 ), the denitrification kinetics of the three Thauera strains became more similar showing a PO type of DRP and prolonged accumulation of NO 2 − and N 2 O (Figure 2 and Table 4), even at an ideal temperature (30 • C).…”
Section: Type and Concentration Of N-sources Affect Denitrification Regulatory Phenotypesmentioning
confidence: 78%
“…In contrast, strain NS1 exhibited similarities to a PO type of DRP and transient accumulation of NO 2 − resulting from reduction of NO 3 − (Figure 1B). This strain is phylogenetically more related to strains K172 and S100 ( > 90% 16S rRNA gene similarity; Suri et al, 2019) but unexpectedly showed lower denitrification rates as compared to the type strain K172 under identical denitrifying culture conditions. At higher NO 3 − concentrations ( > 2 mmol L −1 ), the denitrification kinetics of the three Thauera strains became more similar showing a PO type of DRP and prolonged accumulation of NO 2 − and N 2 O (Figure 2 and Table 4), even at an ideal temperature (30 • C).…”
Section: Type and Concentration Of N-sources Affect Denitrification Regulatory Phenotypesmentioning
confidence: 78%
“…Additionally, sand grains can further mimic environmental conditions in marine sediments, soil and oil reservoir. Currently, sand-packed reactors were used to investigate oil reservoir related studies, such as souring control and enhanced oil recovery (Gieg et al, 2011;Gassara et al, 2015;An et al, 2017;Suri et al, 2019) targeting SRB and nitrate-reducing bacteria. Bioreactor or studies under flow regarding methanogens have been largely neglected due to the difficulties maintaining an anaerobic system that allows methane measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Alkylbenzenes were added directly to 50 mL aqueous CSBK medium or to 1 mL of HMN overlaying this medium to minimize toxicity. A 20-fold concentrated 18PW sample (1 mL) or a nitrate-reducing chemostat culture (5 mL), continuously fed with either toluene or ethylbenzene ( Suri, 2017 ), were used as inocula. However, these were unable to use toluene or ethylbenzene for reduction of 10 mM perchlorate within 30 days of incubation.…”
Section: Resultsmentioning
confidence: 99%